1α, 25-dihydroxyvitamin D3 promotes osseointegration of titanium implant via downregulating AGEs/RAGE pathway in T2DM. Issue 11 (November 2018) - Jia, Tingting; Wang, Ya-nan; Zhang, Dongjiao; Xu, Xin
Abstract : Diabetes-induced advanced glycation end products (AGEs) overproduction would result in compromised osseointegration of titanium implant and high rate of implantation failure. 1α, 25-dihydroxyvitamin D3 (1, 25VD3 ) plays a vital role in osteogenesis, whereas its effects on the osseointegration and the underlying mechanism are unclear. The purpose of this study was to investigate that 1, 25VD3 might promote the defensive ability of osseointegration through suppressing AGEs/RAGE in type 2 diabetes mellitus. In animal study, streptozotocin-induced diabetic rats accepted implant surgery, with or without 1, 25VD3 intervention for 12 weeks. After killing, the serum AGEs level, bone microarchitecture and biomechanical index of rats were measured systematically. In vitro study, osteoblasts differentiation capacity was analyzed by alizarin red staining, alkaline phosphatase assay and Western blotting, after treatment with BSA, AGEs, AGEs with RAGE inhibitor and AGEs with 1, 25VD3 . And the expression of RAGE protein was detected to explore the mechanism. Results showed that 1, 25VD3 could reverse the impaired osseointegration and mechanical strength, which possibly resulted from the increased AGEs. Moreover, 1, 25VD3 could ameliorate AGEs-induced damage of cell osteogenic differentiation, as well as downregulating the RAGE expression. These data may provide a theoretical basis that 1, 25VD3 could work as an adjuvant treatment against poor osseointegration in patients with type 2 diabetes mellitus.